Where Anti-Corruption Education Need To Be Started - Heryadi, Adi; Evianawati, Evianawati; Atmaningrum, Agustin (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2020)
This descriptive research with the survey method aims to determine the level of knowledge and understanding of junior high school students in Sleman, DIY on corruption, and the Corruption Eradication Commission (KPK). The cluster sampling technique was used to obtain data from a total of 20,748 students from 137 junior high schools in Sleman Regency in 2017, through a questionnaire consisted of 10 answer choices. This research was conducted from 21 May to 21 August 2017 and analyzed with the SPSS version 16 with a 95% level of confidence and a margin error of 1.86%.The data collected was descriptive, therefore, it does not need further explanation or test hypotheses (Azwar, 2015). The results of this study are used to determine the intervention steps that need to be taken in anti-corruption campaigns in the millennial generation.